Analysis of fatty composition from different parts of Ganoderma lucidum - Li, Jing-jing; Liu, Jing-jing; Si, Jin-ping; Cao, Long-shu (Zhongguo zhongyao zazhi, 2015)
The oil content and fatty acid composition of Ganoderma lucidum collected from different producing areas, varieties, tissue types and growth periods were measured and analyzed. The results showed that the oil content was 23. 61%-34.17% in different domestic producing areas of China; the oil content of fruiting bodies from major varieties cultured in Zhejiang province were 0.81%-1.87%, wall-unbroken spores were 0.07%-0.24%, wall-broken spores were 27.54%-34.17%, so the oil content of wall-unbroken spores were much higher than fruiting bodies, and wall-breaking treatment would increase the oil extraction rate 150-340 times. G. lucidum spores oil was mainly composed of unsaturated fatty acid composition. oleic acid and linoleic content were 53.26%-58.16% and 10.69%-16.87% respectively. Fatty acid composition ratio of spores and fruiting bodies were significantly different by PLS-DA. Determining the composition of fatty acid, especially the content of oleic acid, stearic acid and palmitic acid, could identify the tissue types of G. lucidum products' sources. In addition, the study result showed that the spores and fruiting bodies collected in the first year contained richer oil and fatty acid than second year's samples from the same variety of G. lucidum.